Association of Depression/Anxiety Symptoms with Neck Pain: A Systematic Review and Meta-Analysis of Literature in China - Fushui Liu; Ting Fang; Fanyuan Zhou; Meimei Zhao; Mei Chen; Jianyu You; Yuli Jin; Jinmei Xie; Zhongyong Liu (Pain Research and Management)
Background. Due to its high morbidity and prevalence, the potential relationships of depression/anxiety symptoms in neck pain (NP) are not well demonstrated. Objectives. This study aimed to conduct a comprehensive estimation of controlled trials of psychological problems and to test hypotheses concerning whether NP was statistically relative to anxiety/depression symptoms. Methods. Chinese literature databases such as the China National Knowledge Infrastructure (CNKI), VIP Information (VIP), Chinese Biomedicine (CBM), and Wanfang Data (WANFANG) were scientifically searched for reports published until February 5, 2018. Controlled trials incorporating NP patients with anxiety/depression versus healthy people were contained. Two researchers screened each article and extracted data, respectively, and blinded to the findings of each other. Meta-analysis was conducted by the Cochrane Collaboration’s RevMan 5.3 and Stata 14.0 (Stata Corp LP, USA) software. Results. We identified 13 eligible studies involving 2339 patients and 3290 healthy people. Compared with healthy control participants, the findings indicated that depression/anxiety symptoms were more common or severe in NP patients (respectively, SMD = 0.89; 95% CI = (0.58, 1.20); P<0.01 and SMD = 0.92; 95% CI = (0.65, 1.20); and P<0.01), results from the pooled data demonstrated no statistical significance between depression/anxiety symptoms and gender in NP patients (resp., SMD = 0.16; 95% CI = (−0.18, 0.51); P=0.35 and SMD = −0.08; 95% CI = (−0.42, 0.27); and P=0.67), and the combined data of the incidence of depression or anxiety symptoms revealed significant difference between NP patients and healthy persons (resp., RR = 4.81; 95% CI = (3.30, 7.01); P<0.01 and RR = 3.29; 95% CI = (2.16, 5.00); and P<0.01). In addition, we did not find articles that met the inclusion criteria, which compared NP patients with other physical illnesses in terms of anxiety/depression symptoms. Conclusions. This meta-analysis suggests that anxiety/depression symptoms are associated with high morbidity in NP patients. We consider these reports support the viewpoint that nonspecific mechanisms mediate mental disturbances in NP. This study may have clinical value for NP, offering an underlying target for the prevention and treatment of anxiety/depression.